(untitled) (Journal of the College of Basic Education, 2022)
nano crystalline CdO films have been deposited by chemical bath deposition technique, where the cadmium acetate salt (Cd(CH3COO)2)used as a source of cadmium ions. The spectral transmission and the optical energy band gap increase from 84% and 2.47eV (for bulk CdO) to 95% and 2.92 eV(for nano CdO) respectively. This has been obtained as a result of quantum confinement with low values of conductivity and carriers mobility.